Introduction BIM in Engineering Curriculum: Student Perspectives from Gaza Strip's Universities - Ismail Al Daoor (International Journal of Engineering and Management Research, 2021)
BIM is one of the most recent acronyms to appear in the world of architecture and construction. However, the Palestinian construction industry is encountering several problems as lack of application modern information technology and the lack of interest in BIM by Palestinian universities in Gaza Strip. So, the universities adopted strategy of using BIM as an innovative technology to allow the acquisition of new skills for student. This paper investigated the current situation and future approaches to incorporating the BIM in the curriculum and main challenges facing the BIM in engineering colleges in Palestinian universities. The population consists of bachelor engineering students; quantitative approach had adopted to collect data by using a questionnaire survey specially prepared for this purpose which was distributed to student. Returned data from 152 engineering students responding to survey were subjected to proper statistical analysis. The results indicated the knowledge about the technique is low, and they were dealing with BIM applications for duration less than one year. Focused recommendation of these results, is containing this technique as educational courses in universities, and updating this courses for suiting the technology changes periodically, providing specialized academics in order to educating and credence it officially.